Neuropsychomotor regression in preschoolers and schoolchildren after the COVID-19 pandemic (Research, Society and Development, 2023)
The period of childhood is the moment of greatest capacity that the nervous system has to reorganize and adapt its neural networks in response to environmental and organic demands, this stage is marked by significant advances in motor, cognitive, psychosocial and language skills, with acquisitions progressively more complex in daily life functions. In addition, neuropsychomotor development (NPMD) is characterized by a process of dynamic evolution, with the presentation of new experiences and stimuli being of paramount importance to the child. However, in 2020, the world was facing a disease with a high level of transmission, requiring social isolation to control the disease, which changed the routine of the entire world population, and it is possible to consider that children were one of the groups most impacted by these changes. Their routines, including social, school and family environments, were profoundly modified, with consequences for the development and well-being of children. That said, the main objective of this work is to analyze the causes and consequences involved in the neuropsychomotor development process of children aged 4-5 years, based on an integrative literature review. In conclusion, it is noted that the pediatric age group had complications not only in relation to the cognitive part of development, but also the physical, emotional and social aspects.